Students’ Perception on the Relative Fairness of Selected Educational Accommodations - Randall, Boen; Thomas, D. Upton; Nicole, Knickmeyer; Azzahrah, Anuar (Faculty of Cognitive Sciences & Human Development UNIMAS, 2016)
The purpose of this study is to assess the relative fairness of selected educational accommodations provided to peers who have disabilities. This study utilized two scales developed by Upton (2000) which quantifies the relative fairness that students perceive towards the provision of selected educational accommodations. The findings of this study yielded evidence to support that level of education at a university level might have an influence on the students’ perceptions about educational accommodations offered to the students with disabilities. These surveys were distributed to around 409 students at a mid-size southern public university in the United States. Implications of these findings and suggestions for future research are provided.